Effect of water stress on growth and antioxidative defence system in Cucumis spp. at seedling stage - MUNDALIA, LALITA; JOSHI, UMA; RAMPURIA, SAKSHI; MEGHWAL, RAJURAM; KUMAR, SUSHIL; SHARMA, RAMAVTAR (The Indian Journal of Agricultural Sciences, 2015)
Drought or moisture stress is one of the most significant environmental stresses causing huge loss to the agriculture worldwide, reducing average yield of major vegetables crop by more than 50%. In the current study, antioxidant responses under water stress were compared to detect water stress tolerant genotypes of Cucumis spp. Forty four genotypes of ten Cucumis spp. were evaluated for their respective drought tolerance and effect of water deficient on various morpho-physiological (root length, shoot length, root and shoot fresh and dry weight) and biochemical [Catalase, Ascorbate peroxidase (APOX) and Guiaicol peroxidase GPOX)] parameters. Of these 44 genotypes, 11.36% were tolerant, 29.54% were moderately tolerant and 38.63% were susceptible and 20.45% were highly susceptible. Decrease in root-shoot length, root-shoot fresh weight, root-shoot dry weight was observed in most of the genotypes. The activity of catalase and GPOX was increased in water deficit conditions while the activity of APOX decreased for most of the genotypes. Though none of the growth parameters and enzyme activity was correlated with tolerance level, various morpho-physiological and biochemical parameters, were associated under control and stress conditions.